3. Award for best «Nursing Oral Presentation» (“Professional autonomy, nurse-physician collaboration & moral distress among European intensive care nurses”). Papathanassoglou EDE, Kalafati M, Karanikola M, Albarran JW. 6th Annual Congress of WFCCN, 2009, Florence, Italy - Karanikola, Maria (My University, 2026)
3. Award for best «Nursing Oral Presentation» (“Professional autonomy, nurse-physician collaboration & moral distress among European intensive care nurses”). Papathanassoglou EDE, Kalafati M, Karanikola M, Albarran JW. 6th Annual Congress of WFCCN, 2009, Florence, Italy
Keywords: Sciences